2010
DOI: 10.1038/nrmicro2452
|View full text |Cite
|
Sign up to set email alerts
|

Viral security proteins: counteracting host defences

Abstract: Interactions with host defences are key aspects of viral infection. Various viral proteins perform counter-defensive functions, but a distinct class, called security proteins, is dedicated specifically to counteracting host defences. Here, the properties of the picornavirus security proteins L and 2A are discussed. These proteins have well-defined positions in the viral polyprotein, flanking the capsid precursor, but they are structurally and biochemically unrelated. Here, we consider the impact of these two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
76
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 131 publications
3
76
0
Order By: Relevance
“…We found evidence for both apoptosis and necrosis amongst infected cells regardless of the EV type, in agreement with data indicating a competition between cell death pathways and picornavirus replication (Agol & Gmyl, 2010). We also observed disruption of the actin cytoskeleton network and that of intercellular junctions as evidenced by the rounding of infected cells.…”
Section: Impairment Of the Bbb By Enterovirusessupporting
confidence: 78%
“…We found evidence for both apoptosis and necrosis amongst infected cells regardless of the EV type, in agreement with data indicating a competition between cell death pathways and picornavirus replication (Agol & Gmyl, 2010). We also observed disruption of the actin cytoskeleton network and that of intercellular junctions as evidenced by the rounding of infected cells.…”
Section: Impairment Of the Bbb By Enterovirusessupporting
confidence: 78%
“…In FMDV replication, the 2BC polypeptide, rather than 3A or 2B, is responsible for the blockage of ER-to-Golgi apparatus traffic (43,44). In view of the observed heterogeneity in protein structure of these small picornavirus proteins, it has been concluded that the mechanisms by which they exert their inhibition of protein secretion must be different (1,12). On the basis of several studies reporting inhibition of protein secretion by picornaviruses or picornavirus nonstructural proteins (8,22,23,47,67), we expected that GLuc would not be released from PV-GLuc-infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…A failure to block protein transport by 3A or other small enterovirus proteins corresponding to those of PV has been reported for many picornaviruses, such as hepatitis A virus, enterovirus 71, Theiler's virus, and rhinovirus 14 (1,12). In FMDV replication, the 2BC polypeptide, rather than 3A or 2B, is responsible for the blockage of ER-to-Golgi apparatus traffic (43,44).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations